2020
DOI: 10.3390/su12031091
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Passive Design Strategies for Residential Buildings in Cold Semi-Arid Climates

Abstract: Buildings are significant drivers of greenhouse gas emissions and energy consumption. Improving the thermal comfort of occupants in free-running buildings and avoiding active and fossil fuel-based systems is the main challenge in many cities worldwide. However, the impacts of passive design measures on thermal comfort in cold semi-arid regions are seldom studied. With the rapid urbanization and the widespread use of personalised heating and cooling systems, there is a need to inform building designers and city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Encinas and De Herde (2013) used the Monte Carlo method with the Spearman coefficient to analyse the thermal discomfort of users in a building in Chile by considering variables related to ventilation, air infiltration and internal loads. Mahar et al (2020) used the Monte Carlo approach to assess design variables in a residential building in Pakistan. The authors used twenty-one design variables, sampled using the Latin Hypercube sampling, by considering both discrete and continuous distribution, depending on the variable.…”
Section: Monte Carlo Methodsmentioning
confidence: 99%
“…Encinas and De Herde (2013) used the Monte Carlo method with the Spearman coefficient to analyse the thermal discomfort of users in a building in Chile by considering variables related to ventilation, air infiltration and internal loads. Mahar et al (2020) used the Monte Carlo approach to assess design variables in a residential building in Pakistan. The authors used twenty-one design variables, sampled using the Latin Hypercube sampling, by considering both discrete and continuous distribution, depending on the variable.…”
Section: Monte Carlo Methodsmentioning
confidence: 99%
“…Sensitivity analysis is a valuable tool for observational studies in buildings and energy simulations to help the design decision-making for bioclimatic and climate-responsive design [38,39]. Sensitivity analysis has been largely applied to explore the parameters of building thermal performance in several applications, such as the impact of climate change on buildings [40], building stock [41], building retrofits [42], calibration of energy models [43] and building design [44].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The results showed that by adopting passive measures in the building envelope, significant energy savings for heating, cooling, lighting, and appliances could be achieved while creating a thermally comfortable indoor environment [30]. Several studies in Pakistan examined the relationship between IEQ, thermal comfort, and passive design measures [8,22,[31][32][33][34][35]. However, no research on reducing the indoor temperature and energy demand for cooling through the building envelope and PEEMs in educational buildings in Karachi, Pakistan, has been conducted.…”
Section: Introductionmentioning
confidence: 99%